Biochemical and clinical response after umbilical cord blood transplant in a boy with early childhood‐onset beta‐mannosidosis. Issue 7 (21st May 2019) - Lund, Troy C.; Miller, Weston P.; Eisengart, Julie B.; Simmons, Katrina; Pollard, Laura; Renaud, Deborah L.; Wenger, David A.; Patterson, Marc C.; Orchard, Paul J
Abstract: Background: Deficiency in the enzyme β‐mannosidase was described over three decades ago. Although rare in occurrence, the presentation of childhood‐onset β‐mannosidase deficiency consists of hypotonia in the newborn period followed by global development delay, behavior problems, and intellectual disability. No effective pharmacologic treatments have been available. Methods: We report 2‐year outcomes following the first umbilical cord blood transplant in a 4‐year‐old boy with early childhood‐onset disease. Results: We show restoration of leukocyte β‐mannosidase activity which remained normal at 2 years posttransplant, and a simultaneous increase in plasma β‐mannosidase activity and dramatic decrease in urine‐free oligosaccharides were also observed. MRI of the brain remained stable. Neurocognitive evaluation revealed test point gains, although the magnitude of improvement was less than expected for age, causing lower IQ scores that represent a wider developmental gap between the patient and unaffected peers. Conclusion: Our findings suggest that hematopoietic cell transplant can correct the biochemical defect in β‐mannosidosis, although preservation of the neurocognitive trajectory may be a challenge. Abstract : UCBT can restore leukocyte and plasma beta‐mannosidase activity and decrease urine‐free oligosaccharides. Neuropsychological evaluation after UCBT showed preservation in some areas, but losses in others.